Factors Affecting Entrepreneurial Intention of Students at The Northern Agriculture and Forestry College - OUNTHAPHANH, Bounleuam; HOONGSENGPHA, Soudthida; SENGCHANH, Souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aims to study the level of importance and the relationship between Factors Affecting Entrepreneurial Intention among Students at the Northern College of Agriculture and Forestry. Using five indicators of intentions in entrepreneurship theory, including Attitudes, Education, Social norms, Recognition of successful entrepreneurship, and Self-motivation, we can analyze the relationships and factors that have an effect on the expectations of students in entrepreneurship. The sample of this research was 80 students who are studying at the Northern College of Agriculture and Forestry. Using a five-level Likert scale questionnaire to collect data, there is a reliability level of 0.911 (91.1%) and SPSS statistical software for data analysis by frequency, percent, mean, standard Deviation, Pearson Correlation coefficient, and Multiple Regression Analysis. The result of the research found that 1) The level of importance of the factors that affect the expectation of entrepreneurship of the students of Northern Agriculture and Forestry College as a whole is at a high level (= 789, SD = 0.583), and the level of expectation of entrepreneurship of the students as a whole is at the highest level (= 4.19, SD = 0.901) and The ability factors have a linear relationship, have an effect in the same direction, and result in the creation of Entrepreneurial intentions among Students at the Northern College of Agriculture and Forestry. They include two factors: Attitudes and Self-Motivation with a statistical significance of 0 and 0.05.